Degradation and stress response mechanism of Cryptococcus podzolicus Y3 on ochratoxin A at the transcriptional level. (1st March 2022) - Wei, Meilin; Dhanasekaran, Solairaj; Yang, Qiya; Ngolong Ngea, Guillaume Legrand; Godana, Esa Abiso; Zhang, Hongyin
Abstract: Ochratoxin A (OTA) is a major mycotoxin contaminant of cereals and grapes. Our previous study proved the ability of Cryptococcus podzolicus Y3 to degrade OTA. The main aim of the present study was to investigate the OTA degradation mechanism by C. podzolicus Y3 using Next-generation sequencing. The results that showed 427 and 100 genes were up- and down-regulated after OTA exposure, respectively. Gene Ontology analysis indicated that genes related to yeast growth, reproduction, and activity were differentially regulated under OTA stress. The results of Kyoto Encyclopedia of Genes and Genomes enrichment showed that OTA stress enhanced energy metabolism, repair DNA and RNA, ribosome biogenesis and peroxisome biogenesis in C. podzolicus Y3. In contrast, OTA treatment inhibited glycosylation modification and degradation of endoplasmic reticulum-related proteins, MAPK signal transduction. Gene function analysis revealed that a biodegradable enzyme, carboxypeptidase A4, possibly catalyzed the amide bonds of OTA. Other essential genes of C. podzolicus Y3 that responded to OTA stress encoded cytochrome P450, zinc finger proteins and heat shock protein 70. However, glutathione S-transferase was not involved in the detoxification of OTA. This study unveiled the possible OTA degradation and response mechanisms of C. podzolicus Y3 at the transcriptional level. Highlights: 527 genes were significantly regulated in C. podzolicus Y3 during OTA stress. CPA4 was potentially contributed to OTA degradation in C. podzolicus Y3. OTA stress induced metabolic pathways and genes contributed to stress response. OTA limited signal transduction and protein modification in C. podzolicus Y3.